Prevalence of hypospadias patients with undescended testis - Abrar Arbhiwa Tanguirsyaf Siregar; Shalita Dastamuar; Theodorus Theodorus; Marta Hendry (Intelektual Pustaka Media Utama, 2019)
Hypospadias is an anomaly of meatus urethra externus on ventral penis. It caused by incomplete fusion of urethral folds. The purpose of this study was to investigate the prevalence of hypospadias with undescended testis in the Department of Surgery Mohammad Hoesin Hospital in Palembang Indonesia. A prevalence study was done in the Medical Records Department of Mohammad Hoesin Hospital from July 2018 to February of 2019. 103 patients met study inclusion criteria. Univariate analysis of the patients’ data was conducted using IBM SPSS Statistics 25. The study found that hypospadias was most common in the age group of 1 to 5 years old (49.5%) and the most common type of hypospadias was severe hypospadias (68.9%). Furthermore, 7 out of 103 patients (6.8%) were hypospadias patients with undescended testis and the most common types of undescended testis among them were bilateral undescended testis and left undescended testis with 3 patients each (42,85%). Prevalence of hypospadias with undescended testis were 7 people (6,8%).